Functional outcome of arthroscopic debridement for massive, irreparable rotator cuff tears - Zanini, Beatrice; Rusconi, Mattia; Fornara, Paolo; Malgrati, Federica; Grassi, Federico Alberto; Leigheb, Massimiliano (Acta Biomedica Atenei Parmensis, 2022)
Rotator cuff tears are a common cause of shoulder pain in the middle-aged population. The treatment of these lesions must be individualized on the basis of the type of patient, the clinical and anatomical picture. Arthroscopic debridement is indicated in painful massive tears, in the absence of severe functional impairment of the shoulder. The aim of this study is the evaluation of the medium term clinical results of this procedure. We retrospectively assessed patients who underwent arthroscopic debridement surgery for massive rotator cuff injury in the period between January 2011 and December 2016 at our institution. A group of patients underwent a follow-up evaluation during which the Constant Score, Oxford Shoulder Score and NRS pain score were compiled. Those who were unable to attend the evaluation were assessed through a telephone questionnaire aimed at investigating pain and degree of satisfaction with the treatment. 93% of patients were satisfied with the results obtained, with an average NRS of 1.31 for patients undergoing the medical examination and 0.68 for patients contacted by telephone. The mean Constant score of the evaluated patients was 75.6 ± sd, with a mean strength of 3.92 ± sd, while the mean value of the Oxford Shoulder Score was 16.8 ± sd. The study suggests that arthroscopic debridement is a viable option for the surgical treatment of massive rotator cuff tears. The clinical results and patient satisfaction are conditioned by the preoperative functional status: an optimal outcome can be expected for painful shoulders with sufficiently preserved active mobility.